"Reverse" sexual dichromatism in a Neotropical frog. (30th August 2019) - Engelbrecht‐Wiggans, Emily; Tumulty, James P.
Abstract: Sexual dichromatism is widespread among animals, but examples of "reverse" sexual dichromatism, in which females are more brightly colored than males, are extremely rare. We discovered a unique case of reverse sexual dichromatism in the golden rocket frog ( Anomaloglossus beebei ), a diurnal Neotropical frog. Females are bright "golden" in color, and males are drab tan with brown pigmentation that darkens when they are calling. Here, we document this color variation with calibrated digital photography and further show that there is no evidence for sex‐specific habitat matching; both sexes live in the same well‐lit habitat on green bromeliad leaves. Our results suggest that color variation in this species is an intraspecific signal and provide an important exception to the general expectation that males are more visually conspicuous in species with conventional sex roles.